Treatment of psoriatic arthritis with biologic and targeted synthetic DMARDs: British Society for Rheumatology guideline scope - Tillett, W; Allen, A; Tucker, L; Chandler, D; Ciurtin, C; Davis, C; Dick, A; Foulkes, A; Gullick, N; Helliwell, P; Jadon, D; Jones, G; et al. (Oxford University Press, 2020)
The aim of this guideline is to provide an update on evidence-based recommendations for treatment of adult patients with PsA. The previous BSR guidelines for PsA were published in 2012 and since that time, there have been many new advanced therapies licensed for PsA. This update will provide practical guidance for clinicians on the optimal selection of advanced therapies taking into account different domains of PsA (arthritis, enthesitis, dactylitis, axial disease and psoriasis) and key associated comorbidities. It will also update guidance on treatment strategy including the use of a treat-to-target approach. The guideline will be developed using the methods and processes outlined in Creating Clinical Guidelines: Our Protocol. (1) This development process to produce guidance, advice and recommendations for practice has National Institute for Health and Care Excellence (NICE) accreditation.